Implementação de um sistema de algoritmos de programação não-linear - Ribeiro, Clóvis Augusto (1973)
This work is the result of the computer implementation of a set of nonlinear programming algorithms destined to solve constrained or unconstrained problems. The methods are concisely discussed after which the corresponding algorithms are presented. As the algorithms are approached from an essentially practical point of view, no original theoretical developments are pursued with the possible exception of some emphasis on the precision manipulations made by the algorithms. The system has been organized in order to provide to the user a good easiness in operation.